2013
DOI: 10.15376/biores.8.4.5761-5772
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Conversion of Lignocellulosic Biomass to Levulinic Acid in Ionic Liquid

Abstract: The catalytic conversion of lignocellulosic biomass to levulinic acid in ionic liquid, [EMIM][Cl] was conducted using a hybrid catalyst. The hybrid catalyst (1:1 ratio) with equal CrCl 3 and HY zeolite weight ratios was synthesized using a wet impregnation method. Initially, optimization of cellulose as a model compound was carried out using two-level full factorial design ( 2 3 ) with two centre points. Under optimum process conditions, 46.0% of levulinic acid yield was produced from cellulose. Subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Ionic liquids are salts consisting of ions which are liquid at ambient temperatures or below 100 • C [135]. The stability, the low vapor pressure, the easy separation and recyclability of ionic liquids, coupled with the fact that their physical and chemical properties can be easily tuned by varying the ions, are some of the important reasons for the intense interest for the use of these solvents to convert raw biomass into added-value products [136][137][138][139][140][141][142]. Catalytic conversion of biomass to LA in the ionic liquid [EMIM][Cl] using a hybrid catalyst (CrCl 3 and HY-zeolite) has shown to yield 46 wt % of LA from cellulose working at 61.8 • C for 14.2 min.…”
Section: Biphasic Systems and Ionic Liquidsmentioning
confidence: 99%
“…Ionic liquids are salts consisting of ions which are liquid at ambient temperatures or below 100 • C [135]. The stability, the low vapor pressure, the easy separation and recyclability of ionic liquids, coupled with the fact that their physical and chemical properties can be easily tuned by varying the ions, are some of the important reasons for the intense interest for the use of these solvents to convert raw biomass into added-value products [136][137][138][139][140][141][142]. Catalytic conversion of biomass to LA in the ionic liquid [EMIM][Cl] using a hybrid catalyst (CrCl 3 and HY-zeolite) has shown to yield 46 wt % of LA from cellulose working at 61.8 • C for 14.2 min.…”
Section: Biphasic Systems and Ionic Liquidsmentioning
confidence: 99%
“…It is rather surprising that the same attention has not been paid to LA production, to the extent that no work in this direction had been conducted till 2011 [57]. Recently, though, Ya'aini and Amin have reported the use of the ionic liquid [EMIM]Cl for LA production [266]. A hybrid CrCl 3 -HY zeolite catalyst was used, and a yield of 46 wt% was obtained from cellulose, and 20 and 17 wt% from empty fruit bunch and kenaf.…”
mentioning
confidence: 99%
“…Recent studies showed the possibly of one-pot production of LA and LE from various lignocellulosic biomasses via various catalytic methods, including wheat straw, ,, bamboo, ,, oil palm biomass such as empty fruit bunch, fronds, and kenaf, ,,, sorghum grain, marine biomass, , bagasse, , rice husk, rice straw, switchgrass, wood chips, and paper pulp as well as paper waste . Nevertheless, the use of ILs for the one-pot production of LA and LE from various lignocellulosic biomasses is still at the developing stage, with limited research reported, ,,,, which will be critically discussed in Section . As shown in Figure , the ILs-catalyzed strategy allows the discarding of the biomass pretreatment step, thereby giving a shorter process compared to the conventional strategy.…”
Section: Biomass Pretreatment With Ilsmentioning
confidence: 99%
“…Table S3 of the Supporting Information summarize the pertinent references on the direct conversions of biomass to LA ,,,, and LE via ILs. The theoretical yield of LA/LE is determined based on a given cellulose content of biomass, whereas the process efficiency refers to the efficiency of biomass conversion to LA/LE based on the theoretical yield.…”
Section: Conversions From Biomass and Its Derivatives To La And Lementioning
confidence: 99%